Low-temperature sintered silver paste and preparation method and application thereof
By adding molten substances and dispersants to the low-temperature sintered silver paste, it ensures that it maintains wettability and sintering at high temperatures, solving the problem of insufficient shear strength of the low-temperature sintered silver paste, and achieving the improvement of high shear strength and thermal conductivity , reduces costs and avoids the shear strength of traditional solder when stored at high temperatures.
Patent Information
- Application Number
- CN202411158858.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2024-12-13
AI Technical Summary
The low-temperature sintered silver paste has low shear strength after the surface is dry, making it difficult to meet the needs of high-power flip LED chip electrode connections. At the same time, traditional solder materials such as gold-tin alloys have high cost and poor heat resistance have problems.
Provide a low-temperature sintered silver paste, whose coating is solid at room temperature, becomes a liquid state and restores wettability at around 100°C. Sintered above 180°C to form an irreversible solid state, combining silver powder, dispersant, molten substance and solvent. , ensuring high shear strength and thermal conductivity are maintained during high and low temperature cycles and high temperature storage.
The low-temperature sintered silver paste maintains high shear strength and thermal conductivity after high temperature storage, reducing material costs, and avoiding the problem of reducing shear strength of traditional solder during high temperature storage.
Smart Images

Figure BDA0005005859880000071 
Figure BDA0005005859880000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of silver paste, and in particular to a low-temperature sintered silver paste and a preparation method and application thereof. Background Art
[0002] In the application of electrode connection of high-power flip-chip LED chips, eutectic welding technology is generally used. This welding method has high thermal conductivity, electrical conductivity and high mechanical strength characteristics, and can achieve a crack-free and firm bond between the pad and the chip. This is usually a use scenario that requires heat resistance. Traditionally, gold-tin alloy is used as a welding material, which has the advantages of fast heat dissipation, good high-temperature stability, easy wetting, good conductivity and good oxidation resistance. However, the high cost of gold-tin alloy is a more significant problem. In addition, common lead-tin solder has the problem of poor heat resistance.
[0003] Low-temperature sintering silver paste is also a semiconductor packaging material. After sintering, its melting point can be raised to 960°C, but its surface drying process is irreversible. Generally, the device is made in a wet state before the coating is dried, and then sintered. However, the flip chip electrode needs to be in a dry solid state to facilitate storage and transportation, and then made into a device. Under this series of conditions, the coating loses its wettability after the low-temperature sintering silver paste is dried, and the shear strength of the subsequent device is low, so it is difficult to meet the application in the electrode connection of high-power flip-chip LED chips.
[0004] Therefore, it is necessary to make technical improvements to the low-temperature sintering silver paste so that it can have the advantages of strong temperature resistance of the low-temperature sintering silver paste while improving its shear strength and making it suitable for the preparation of flip-chip electrodes. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a low-temperature sintering silver paste. The coating made of the low-temperature sintering silver paste of the present invention is solid at room temperature after surface drying. When heated to about 100°C, the coating becomes liquid and restores wettability. After heating to above 180°C, the resin decomposes, the silver paste begins to sinter, and the coating becomes solid again. This change process is irreversible. Therefore, the electrode made of the low-temperature sintering silver paste of the present invention is solid, which is convenient for storage and transportation. At the same time, it has the advantage of strong temperature resistance of the low-temperature sintering silver paste, and maintains a high shear strength after high and low temperature cycles or high-temperature storage. In addition, the low-temperature sintering silver paste of the present invention has the advantages of high thermal conductivity and low volume resistivity after sintering.
[0006] The invention also provides a method for preparing the low-temperature sintering silver paste.
[0007] The invention also provides a flip chip electrode.
[0008] The invention also proposes the application of the low-temperature sintered silver paste in chip electrode welding.
[0009] In a first aspect of the present invention, a low-temperature sintering silver paste is provided, wherein the raw materials include silver powder, a dispersant, a molten material and a solvent;
[0010] Wherein, the molten material is an organic matter with a melting point of 30 to 100°C.
[0011] According to a specific embodiment of the present invention, the low-temperature sintering silver paste of the present invention has at least the following beneficial effects:
[0012] The coating made of the low-temperature sintered silver paste of the present invention is solid at room temperature after the surface is dried. When heated to about 100°C, the coating becomes liquid and restores wettability. After being heated to above 180°C, the resin decomposes, the silver paste begins to sinter, and the coating becomes solid again. This change process is irreversible. Therefore, the electrode made of the low-temperature sintered silver paste of the present invention is solid, which is convenient for storage and transportation. At the same time, it has the advantages of strong temperature resistance of the low-temperature sintered silver paste, and maintains high shear strength after high and low temperature cycles or high-temperature storage. In addition, the low-temperature sintered silver paste of the present invention has the advantages of high thermal conductivity and low volume resistivity after sintering, and the cost is low.
[0013] According to some embodiments of the present invention, the raw material composition includes, by mass, 83 to 92 parts of silver powder, 1 to 2.5 parts of dispersant, 2.5 to 5.5 parts of molten material and 3 to 10 parts of solvent.
[0014] According to some embodiments of the present invention, the raw material composition includes, by mass, 85 to 90 parts of silver powder, 1 to 2 parts of dispersant, 3 to 5 parts of molten material and 3 to 10 parts of solvent.
[0015] According to some embodiments of the present invention, the raw material composition includes, by mass, 85 to 90 parts of silver powder, 1 to 2 parts of dispersant, 3 to 5 parts of molten material and 3 to 8 parts of solvent.
[0016] According to some embodiments of the present invention, the molten material comprises at least one of polyethylene glycol, polytetrahydrofuran or D-sorbitol.
[0017] The molten material is solid at room temperature and becomes liquid after heating. The present invention finds that the addition of the molten material provides the silver paste with wetting properties under heating conditions. The content of the molten material in the silver paste needs to be within a suitable range to ensure a higher shear strength of the prepared chip electrode.
[0018] According to some embodiments of the present invention, the molecular weight of the polyethylene glycol is 500-9000.
[0019] According to some embodiments of the present invention, the molecular weight of the polytetrahydrofuran is 2000-4000.
[0020] According to some embodiments of the present invention, the dispersant is a water-soluble thermoplastic resin.
[0021] According to some embodiments of the present invention, the dispersant comprises at least one of polyvinyl alcohol, polyacrylamide or polyacrylic acid.
[0022] The water-soluble thermoplastic resin is added to the low-temperature sintered silver paste of the present invention to play a good dispersing effect on the silver powder. After exploration, it is found that the usage ratio of the water-soluble thermoplastic resin to the silver powder needs to be greater than 1:90 to ensure full dispersion and avoid agglomeration to affect product performance.
[0023] According to some embodiments of the present invention, the degree of polymerization of the polyvinyl alcohol is 1000-2000.
[0024] According to some embodiments of the present invention, the silver powder is nano silver powder with a particle size ranging from 100 to 400 nm.
[0025] The silver powder in the low-temperature sintering silver paste diffuses into the gold-plated layer of the wafer during the sintering process and provides shear strength.
[0026] According to some embodiments of the present invention, the specific surface area of the silver powder is less than 4 m 2 / g,
[0027] According to some embodiments of the present invention, the melting point of the silver powder is less than 180°C.
[0028] According to some embodiments of the invention, the solvent comprises propylene glycol and water.
[0029] According to some embodiments of the present invention, the mass concentration of propylene glycol in the solvent is 10% to 70%.
[0030] The second aspect of the present invention provides a method for preparing the low-temperature sintering silver paste according to the first aspect of the present invention, comprising the following steps:
[0031] The dispersant and the molten material are added to the solvent and mixed to obtain a dispersed phase, and then silver powder is added and dispersed using a disperser to obtain a low-temperature sintered silver paste.
[0032] According to some embodiments of the present invention, the dispersion parameter is dispersion at a speed of 1000 to 2000 r / min for 1 to 5 min.
[0033] A third aspect of the present invention provides a flip chip electrode, which is prepared by a method comprising the following steps:
[0034] The low-temperature sintered silver paste described in the first aspect of the present invention is printed on the gold-plated electrode of the wafer, the printing thickness of the silver paste is controlled to be 6-12 μm, and it is baked at 60-100° C. for 30-90 minutes. The wafer is then cut and coated for protection to obtain a flip-chip electrode.
[0035] The fourth aspect of the present invention provides the use of the low-temperature sintering silver paste described in the first aspect of the present invention in chip electrode welding.
[0036] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. DETAILED DESCRIPTION
[0037] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0038] If the specific conditions are not specified in the specific implementation mode, the conventional conditions or the conditions recommended by the manufacturer are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased from the market.
[0039] The nano silver powder in the specific implementation manner was purchased from Laiwu Dada Alloy Co., Ltd.; the polyvinyl alcohol was polyvinyl alcohol 1799 type purchased from McLean; the polyethylene glycol was polyethylene glycol 6000 analytical grade purchased from Komiou; and the molecular weight of polytetrahydrofuran was 3000 purchased from McLean.
[0040] Example 1
[0041] The present embodiment provides a low-temperature sintering silver paste suitable for eutectic welding electrodes, and provides the low-temperature sintering silver paste and a method for preparing LED flip chip electrodes using the same.
[0042] The raw materials for preparing the low-temperature sintering silver paste of this embodiment are calculated by weight: 90 parts of nano silver powder, 2 parts of dispersant, 3 parts of molten material and 5 parts of solvent;
[0043] Among them, the nano silver powder has an average particle size of 300nm and a specific surface area of 3.2m 2 / g, melting point is 160℃, dispersant is polyvinyl alcohol, molten substance is polyethylene glycol. Solvent is propylene glycol and deionized water, with 1 part of propylene glycol and 4 parts of deionized water in the solvent.
[0044] This embodiment provides a method for preparing the low-temperature sintering silver paste, and the specific steps are as follows:
[0045] According to the mass fractions of the above raw materials, the dispersant, the molten material and the solvent are fully mixed and dissolved, and then the solution is mixed with the silver powder, and dispersed for 2 minutes using a gravity disperser at a speed of 1500r / min to obtain a uniformly mixed silver paste;
[0046] This embodiment provides a method for preparing LED flip chip electrodes by low temperature sintering silver paste, and the specific steps are as follows:
[0047] Print photoresist on sapphire wafer material (omitting wafer casting and other processes), use exposure and development processes to control the shape of the photoresist on the sapphire wafer to be 2mm×2mm square, then use PVD coating to coat various metals, and finally coat a 200nm thin gold layer as an indirect adhesion layer, print the silver paste prepared above, control the thickness of the silver paste to be 8-10μm, bake at 80℃ for 60min to remove the solvent, cut the wafer and coat it with a protective film to obtain the LED flip chip electrode.
[0048] Example 2
[0049] The present embodiment provides a low-temperature sintering silver paste suitable for eutectic welding electrodes, and provides the low-temperature sintering silver paste and a method for preparing LED flip chip electrodes using the same.
[0050] The raw materials for preparing the low-temperature sintering silver paste of this embodiment are as follows by mass: 90 parts of nano silver powder, 1 part of dispersant, 4 parts of molten material and 5 parts of solvent;
[0051] The nano silver powder is the same as that in Example 1, the dispersant is polyvinyl alcohol, the molten material is polytetrahydrofuran, and the solvent is propylene glycol and deionized water, wherein the solvent contains 1 part of propylene glycol and 4 parts of deionized water.
[0052] The method for preparing the low-temperature sintered silver paste and the method for preparing LED flip chip electrodes using the low-temperature sintered silver paste in this embodiment are the same as those in Example 1.
[0053] Example 3
[0054] The present embodiment provides a low-temperature sintering silver paste suitable for eutectic welding electrodes, and provides the low-temperature sintering silver paste and a method for preparing LED flip chip electrodes using the same.
[0055] The raw materials for preparing the low-temperature sintering silver paste of this embodiment are calculated by weight: 90 parts of nano silver powder, 2 parts of dispersant, 5 parts of molten material and 3 parts of solvent;
[0056] The nano silver powder is the same as that in Example 1, the dispersant is polyvinyl alcohol, the molten material is D-sorbitol, the solvent is propylene glycol and deionized water, and the solvent contains 0.5 parts of propylene glycol and 2.5 parts of deionized water.
[0057] The method for preparing the low-temperature sintered silver paste and the method for preparing LED flip chip electrodes using the low-temperature sintered silver paste in this embodiment are the same as those in Example 1.
[0058] Example 4
[0059] The present embodiment provides a low-temperature sintering silver paste suitable for eutectic welding electrodes, and provides the low-temperature sintering silver paste and a method for preparing LED flip chip electrodes using the same.
[0060] The raw materials for preparing the low-temperature sintering silver paste of this embodiment are calculated by weight: 85 parts of nano silver powder, 1.5 parts of dispersant, 3.5 parts of molten material and 10 parts of solvent;
[0061] The nano silver powder is the same as that in Example 1, the dispersant is polyvinyl alcohol, the molten material is polyethylene glycol, the solvent is propylene glycol and deionized water, and the solvent contains 7 parts of propylene glycol and 3 parts of deionized water.
[0062] The method for preparing the low-temperature sintered silver paste and the method for preparing LED flip chip electrodes using the low-temperature sintered silver paste in this embodiment are the same as those in Example 1.
[0063] Example 5
[0064] The present embodiment provides a low-temperature sintering silver paste suitable for eutectic welding electrodes, and provides the low-temperature sintering silver paste and a method for preparing LED flip chip electrodes using the same.
[0065] The raw materials for preparing the low-temperature sintering silver paste of this embodiment are calculated by weight: 87 parts of nano silver powder, 2 parts of dispersant, 4.5 parts of molten material and 6.5 parts of solvent;
[0066] The nano silver powder is the same as that in Example 1, the dispersant is polyvinyl alcohol, the molten material is polytetrahydrofuran and D-sorbitol, 4 parts of polytetrahydrofuran and 0.5 parts of D-sorbitol, the solvent is propylene glycol and deionized water, and the solvent contains 3.5 parts of propylene glycol and 3 parts of deionized water.
[0067] The method for preparing the low-temperature sintered silver paste and the method for preparing LED flip chip electrodes using the low-temperature sintered silver paste in this embodiment are the same as those in Example 1.
[0068] Comparative Example 1
[0069] This comparative example provides a low-temperature sintered silver paste, and provides a preparation method of the low-temperature sintered silver paste and a method for preparing an LED flip chip electrode using the same.
[0070] The raw materials for preparing the low-temperature sintering silver paste of this comparative example are calculated by weight: 90 parts of nano silver powder, 1 part of dispersant and 5 parts of solvent;
[0071] The nano silver powder is the same as that in Example 1, the dispersant is polyvinyl alcohol, the solvent is propylene glycol and deionized water, and the solvent contains 1 part of propylene glycol and 4 parts of deionized water.
[0072] The preparation method of the low-temperature sintered silver paste in this comparative example and the preparation method of using the low-temperature sintered silver paste to prepare LED flip chip electrodes are the same as those in Example 1.
[0073] Comparative Example 2
[0074] This comparative example provides a low-temperature sintered silver paste, and provides a preparation method of the low-temperature sintered silver paste and a method for preparing an LED flip chip electrode using the same.
[0075] The raw materials for preparing the low-temperature sintering silver paste of this comparative example are calculated by weight: 85 parts of nano silver powder, 1 part of dispersant, 6 parts of molten material and 8 parts of solvent;
[0076] The nano silver powder is the same as that in Example 1, the dispersant is polyvinyl alcohol, the molten material is polyethylene glycol, the solvent is propylene glycol and deionized water, and the solvent contains 4 parts of propylene glycol and 4 parts of deionized water.
[0077] The preparation method of the low-temperature sintered silver paste in this comparative example and the preparation method of using the low-temperature sintered silver paste to prepare LED flip chip electrodes are the same as those in Example 1.
[0078] Comparative Example 3
[0079] This comparative example provides a low-temperature sintered silver paste, and provides a preparation method of the low-temperature sintered silver paste and a method for preparing an LED flip chip electrode using the same.
[0080] The raw materials for preparing the low-temperature sintering silver paste of this comparative example are calculated by weight: 83 parts of nano silver powder, 1 part of dispersant, 4 parts of molten material and 12 parts of solvent;
[0081] The nano silver powder is the same as that in Example 1, the dispersant is polyvinyl alcohol, the molten material is polyethylene glycol, the solvent is propylene glycol and deionized water, and the solvent contains 5 parts of propylene glycol and 7 parts of deionized water.
[0082] The preparation method of the low-temperature sintered silver paste in this comparative example and the preparation method of using the low-temperature sintered silver paste to prepare LED flip chip electrodes are the same as those in Example 1.
[0083] Comparative Example 4
[0084] This comparative example provides a conventional LED flip chip electrode using a gold-tin alloy as a soldering material, wherein the mass ratio of gold to tin in the gold-tin alloy is 80:20.
[0085] Photoresist is printed on the sapphire wafer material, and the shape of the photoresist on the sapphire wafer is controlled to be a 2mm×2mm square using the exposure and development process. Then, various metals are plated using PVD coating, and finally, gold-tin alloy is plated as an electrode. The gold-tin alloy is plated 1μm each time by PVD, and the total thickness is 4-6μm. After the electrode is made, the photoresist is removed with a blue film, the wafer is cut and coated for protection, and the LED flip chip electrode is obtained.
[0086] Comparative Example 5
[0087] This comparative example provides a conventional LED flip chip electrode using solder paste as a soldering material, wherein the solder paste is SAC 305 purchased from Jiangsu Yinjiuzhou.
[0088] Print photoresist on the sapphire wafer material, use exposure and development process to control the shape of the photoresist on the sapphire wafer to be 2mm×2mm square, then apply flux paste (RMA-218 purchased from KINGBAO), dispense the above solder paste, heat the electrode to 250℃, start cooling after the solder paste melts, control the diameter of the solder ball to 8-10μm, use blue film to remove the photoresist, cut the wafer and cover it with film for protection (associated mucous film test), and then obtain the LED flip chip electrode.
[0089] The comparison of the silver paste raw materials and their usage in each embodiment and comparative example is shown in Table 1.
[0090] Table 1 Silver paste raw materials and their dosage in each embodiment and comparative example
[0091]
[0092] Test Case
[0093] Performance tests were performed on the low-temperature sintered silver pastes prepared in the embodiments and comparative examples and the flip-chip electrodes prepared therefrom.
[0094] 1. Shear strength test:
[0095] First, prepare the eutectic welding electrode shear strength test piece: after the flip chip electrode wafer is cut, it is placed on the gold-plated DBC board, coated with a certain amount of flux paste, and sintered. The sintering welding conditions are: temperature 280℃, pressure 10MPa, sintering time 10min, and air atmosphere;
[0096] The test piece was subjected to a shear strength test (T / CASA 018-2021). A DAGE 4000 shear force tester was used to apply a thrust to the chip part of the device. The speed was set to 300 μm / s and the height was set to 100 μm. The maximum thrust when the chip fell off was recorded and the shear strength was calculated.
[0097] After that, the shear strength performance test of the flip chip electrode after high-low temperature cycling and high-temperature storage was carried out: the flip chip electrode was cycled at -40℃~150℃ (30min / cycle) for 1000h and stored at 250℃ for 1000h, and then the above shear strength test was carried out.
[0098] 2. Volume resistivity test:
[0099] Print silver paste or solder on a glass sheet in the shape of a 8cm×1cm rectangle, bake it at 80°C in air for 60 minutes, and then sinter it at 280°C for 10 minutes to obtain a volume resistivity test piece. Use the four-probe method to test the volume resistivity of the test piece. For gold-tin alloy, use gold finger tape to stick a 8cm×1cm rectangular shape on a glass substrate, remove the tape after PVD plating to make a test piece, and then test it.
[0100] 3. Thermal conductivity test:
[0101] Pour silver paste or solder into a 10mm×10mm×2mm cubic silicone mold, evacuate to remove bubbles, bake for 60 minutes at 80°C in an air atmosphere, and sinter at 280°C for 10 minutes. Take out the thermal conductivity test piece, test the thermal diffusivity using the laser thermal conductivity method (T.CASA 020-2021), test the density using the drainage method, and test the specific heat capacity using DSC to calculate the thermal conductivity. When testing the gold-tin alloy, cut the alloy into the same cube shape for testing.
[0102] 4. Surface dryness test:
[0103] Print the silver paste on the gold-plated DBC board, bake at 80°C for 10 minutes, cover with a protective blue film, leave for 24 hours, then tear off the blue film at the smallest angle to observe whether the silver paste adheres to the blue film. Other materials can be directly made into electrodes according to the examples and then attached with a blue film for testing.
[0104] The test results are shown in Table 2.
[0105] Table 2 Performance test results of low temperature sintered silver pastes prepared in various embodiments and comparative examples and flip chip electrodes prepared therefrom
[0106]
[0107] It can be seen from the above test results that the eutectic welding electrode prepared by the low-temperature sintering silver paste prepared by the scheme of the present invention has a higher shear strength, especially after high and low temperature cycles and high-temperature storage, it can still maintain a higher shear strength. In Comparative Example 5, which uses traditional solder paste as a welding material, the shear strength of the flip-chip electrode prepared by it is greatly reduced after high-temperature storage, mainly because its solder will re-melt during high-temperature storage, which can easily cause the device to be damaged. Although the flip-chip electrode with gold-tin alloy as solder in Comparative Example 4 can solve the problems of shear strength and shear strength after high-temperature storage, its material cost is relatively high. In addition, the test piece prepared by the low-temperature sintering silver paste prepared by the present invention has a lower volume resistivity, which is improved compared to Comparative Examples 4 and 5 using traditional solders, and because the main component of the low-temperature sintering silver paste used in the scheme of the present invention is silver, due to its own properties, it has a higher thermal conductivity, which helps to avoid the heat dissipation of the heat generated during the operation of the chip and improve the performance and durability of the chip product.
[0108] It can be seen from Examples 1 to 3 that as the content of molten material increases, the shear strength of the low-temperature sintered silver paste test piece will increase accordingly. However, in Comparative Example 2, due to the excessively high content of molten material, the shear strength of the flip chip electrode decreases significantly, and has an adverse effect on the resistivity. In addition, the lack of molten material in Comparative Example 1 causes the coating to be unable to be remelted, and the subsequent coating and pad cannot be connected, so the shear strength is 0, which is not suitable for the preparation of flip chip electrodes. In Comparative Example 3, due to the excessively high solvent content of the low-temperature sintered silver paste, the coating cannot be completely dried on the surface under the existing process, and a mucous membrane phenomenon occurs in the surface drying test, indicating that the electrode is in a wet state at this time and cannot be transported or stored subsequently.
[0109] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A low temperature sintering silver paste, characterized in that: The raw material composition includes silver powder, dispersant, molten material and solvent; Wherein, the molten material is an organic matter with a melting point of 30 to 100°C.
2. The low temperature sintering silver paste according to claim 1, characterized in that: The raw material composition comprises, by weight, 83 to 92 parts of silver powder, 1 to 2.5 parts of a dispersant, 2.5 to 5.5 parts of a molten material and 3 to 10 parts of a solvent.
3. The low temperature sintering silver paste according to claim 1 or 2, characterized in that: The molten material includes at least one of polyethylene glycol, polytetrahydrofuran or D-sorbitol.
4. The low temperature sintering silver paste according to claim 1 or 2, characterized in that: The dispersant is a water-soluble thermoplastic resin.
5. The low temperature sintering silver paste according to claim 4, characterized in that: The dispersant includes at least one of polyvinyl alcohol, polyacrylamide or polyacrylic acid.
6. The low temperature sintering silver paste according to claim 1 or 2, characterized in that: The silver powder is nano silver powder with a particle size ranging from 100 to 400 nm.
7. The low temperature sintering silver paste according to claim 1 or 2, characterized in that: The solvents include propylene glycol and water.
8. The method for preparing a low-temperature sintering silver paste according to any one of claims 1 to 7, characterized in that: The following steps are involved: The dispersant and the molten material are added to the solvent and mixed to obtain a dispersed phase, and then silver powder is added and dispersed using a disperser to obtain a low-temperature sintered silver paste.
9. A flip chip electrode, characterized in that: The flip chip electrode is prepared by a method comprising the following steps: On the gold-plated electrode of the wafer, print the low-temperature sintered silver paste described in any one of claims 1 to 7, control the printing thickness of the silver paste to be 6 to 12 μm, bake at 60 to 100° C. for 30 to 90 minutes, then cut the wafer, and coat it with a film for protection to obtain a flip-chip electrode.
10. Use of the low-temperature sintered silver paste according to any one of claims 1 to 7 in chip electrode welding.
